International Community Service Program: Enhancing Islamic Financial Literacy in Thai Islamic Boarding Schools - Fadhilah, Nurul; Nur, Ahmad; Maamor, Selamah; Nuryadin, M. Birusman Nuryadin; Tikawati, Tikawati; Ramah, Fitria; Yanti, Dharma; Parlina , Tika (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: Samakisast Wittaya School is an Islamic educational institution that inherently integrates Islamic values in its curriculum. This Islamic boarding school not only aims to educate students in religious aspects but also in academic and practical aspects of life, including finance. In Thailand, the Muslim population, particularly in the Sadao region, has limited access to financial education that complies with sharia principles. Introducing sharia financial literacy in Islamic schools such as Samakisast Wittaya School can help overcome this gap. Although Thailand has several Islamic financial institutions, the dissemination of information and understanding about these products and services is still limited, especially among Muslim communities in remote or minority areas. Contribution: Increasing sharia financial literacy can help students and surrounding communities become more economically independent, opening up opportunities for entrepreneurship in accordance with sharia law. The importance of sharia financial literacy in Islamic educational institutions such as the Samakisast Wittaya School in Sadao, Thailand, is very significant in helping the development of the community as a whole. Method: The implementation method is through counseling accompanied by interactive discussions. The target is the students of Samakisasst Wittaya School, Sadao, Thailand, totaling 60 students. The problem that arose during the discussion was the issue of the financial attitudes and behavior of students who did not understand correct financial planning, and did not understand the priority scale of primary, secondary and tertiary needs. Results: The team provides solutions regarding the correct meaning of wealth, saving discipline, and the need to make correct financial planning to achieve individual financial resilience. Conclusion: Community service has opened students' thinking and awareness of the importance of students' financial literacy.